2019
DOI: 10.1111/1365-2656.13088
|View full text |Cite
|
Sign up to set email alerts
|

Latitude‐associated evolution and drivers of thermal response curves in body stoichiometry

Abstract: 1. Trait-based studies are needed to understand the plastic and genetic responses of organisms to warming. A neglected organismal trait is elemental composition, despite its potential to cascade into effects on the ecosystem level.2. Warming is predicted to shape elemental composition through shifts in storage molecules associated with responses in growth, body size and metabolic rate. Our goals were to quantify thermal response patterns in body composition and to obtain insights into their underlying drivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…Combining current transcriptomic results and the phenotypic companion study (Van Dievel et al, 2019) suggests that southern populations can increase their growth rate with mild warming despite a lack of major plastic gene expression responses as observed in the northern populations. Unfortunately, our functional analysis does not pinpoint pathways crucial for southern populations to thermally adapt to warming.…”
Section: Gene Pathways Associated With Mild Warmingmentioning
confidence: 79%
See 3 more Smart Citations
“…Combining current transcriptomic results and the phenotypic companion study (Van Dievel et al, 2019) suggests that southern populations can increase their growth rate with mild warming despite a lack of major plastic gene expression responses as observed in the northern populations. Unfortunately, our functional analysis does not pinpoint pathways crucial for southern populations to thermally adapt to warming.…”
Section: Gene Pathways Associated With Mild Warmingmentioning
confidence: 79%
“…Several studies have shown latitude-associated thermal adaptation in I. elegans for life history, behaviour and physiology with cold-adapted northern populations and warm-adapted southern populations (e.g. De Block et al, 2013;Debecker & Stoks, 2019;Van Dievel et al, 2019).…”
Section: Study Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the lifespan of the study species is ca 10 days (Cordero et al ), the loss of a few days has strong fitness implications. The study species shows striking latitudinal differences in life history, with higher larval growth rates in the multivoltine (3–4 generations per year), low‐latitude populations compared to the semivoltine (2 years per generation), high‐latitude populations (Stoks and De Block , Shama et al , Stoks et al , Debecker et al , Debecker and Stoks , Van Dievel et al , Verheyen and Stoks ). Moreover, we have recently shown in separate studies that the low‐latitude populations of the species have a longer adult lifespan (reported as Supporting Information in Debecker et al ) and higher levels of antioxidant enzymes in the larval stage (Debecker and Stoks ).…”
Section: Introductionmentioning
confidence: 89%